2020
DOI: 10.1177/0146167220929203
|View full text |Cite
|
Sign up to set email alerts
|

Mistaking an Intention for a Behavior: The Case of Enacting Behavioral Decisions Versus Simply Intending to Enact Them

Abstract: Five experiments investigated a previously unrecognized phenomenon—remembering that one enacted a mundane behavioral decision when one only intended to do so—and its psychological mechanisms. The theoretical conceptualization advanced in this research proposes that this error stems from a misattribution when an intention and a behavior are similar. Intentions and behaviors are similar when the physical aspects of the behavior resemble the intention (e.g., both require similar keystrokes) and when the behavior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Third, these studies focused on self-reported sharing intentions. Intentions are important precursors of behavior (Albarracin et al, 2021), but it would be useful to test these relationships in the context of actual sharing behavior. Fourth, although we experimentally manipulated self and social relevance and examined mediation within-person, it is possible that unmeasured variables influenced the observed results.…”
Section: Discussionmentioning
confidence: 99%
“…Third, these studies focused on self-reported sharing intentions. Intentions are important precursors of behavior (Albarracin et al, 2021), but it would be useful to test these relationships in the context of actual sharing behavior. Fourth, although we experimentally manipulated self and social relevance and examined mediation within-person, it is possible that unmeasured variables influenced the observed results.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that intentions and behaviors can be similar, leading to errors in recalling mundane decisions (Oliva et al ., 2022). Furthermore, the Theory of Planned Behavior (TPB) suggests that behavioral intentions are strong predictors of actual behavior, with desire and intention implementation proposed to bridge any gaps in the TPB model (Albarracín et al ., 2020). Additionally, the gap between intention and behavior is highlighted in the context of digital contact tracing apps, where social norms play a crucial role in bridging this divide, indicating that intentions do not always translate into actual adoption behaviors (Yao-Hui et al ., 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Third, these studies focused on self-reported sharing intentions rather than actual sharing behavior. Although intentions are important precursors of behavior (Albarracin et al, 2021), it would be useful to test these relationships in additional, ecologically valid contexts, for example by asking participants to actually share the articles on social media or with someone they know. Fourth, although we experimentally manipulated self and social relevance and examined mediation within-person, it is possible that unmeasured variables influenced the observed results.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%